Ambient noise levels of seismic stations located in urban agglomerations in central Inner Mongolia, China. - Wenchao Bao; Quan An; Ye Guo; Lujun Wang; Jianxin Gao (PLoS ONE)
Analysis of the continuous ambient noise data collected by a dense network of broadband seismic stations reveals the characteristics of ambient noise in densely populated urban areas. A study conducted in central Inner Mongolia utilized ten broadband stations to investigate two distinct repetitive and intense noise signals with predominant frequencies ranging from 1-20 Hz and 0.01-1 Hz. The ambient noise within the 0.01-20 Hz frequency range was assessed using Probability Density Function (PDF) and Power Spectral Density (PSD) approaches, and the stations were categorized according to their noise levels. The research results indicate that stations located in urban agglomerations are subject to varying degrees of noise interference, with the main sources of interference being human activities, traffic vibrations, and industrial noise. The impact of high-frequency noise on stations is inversely correlated with the distance from the noise source. Among them, four stations are affected by three noise sources. Three stations are affected by two noise sources, and three stations are affected by one noise source. Therefore, the development of urban agglomerations has brought a large number of noise sources to the stations, which greatly affects the data quality of the stations. This finding urges further investigation on the human activities, traffic vibrations, and industrial noise, and suggests that the station construction should be far away from the urban agglomeration.